Young, low-parity women: Critical target group for family planning in Bangladesh - M. Alauddin; Mark VanLandingham (Asia-Pacific Population Journal, 1989)
After years of persistent low levels, contraceptive prevalence in Bangladesh is beginning to rise, albeit slowly (figure 1). This occurs none too soon. Bangladesh, densely populated and poor, endures a population growth rate that is still quite high, even by third world standards.